A personalized and systematically designed adherence intervention improves photoprotection in adults with xeroderma pigmentosum (XP): results of the XPAND randomized controlled trial - Walburn, Jessica; Norton, Sam; Sarkany, Robert; Canfield, Martha; Sainsbury, Kirby; McCrone, Paul; Araújo-Soares, Vera; Morgan, Myfanwy; Boadu, Janette; Foster, Lesley; Heydenreich, Jakob; Mander, Adrian P; et al. (British journal of dermatology, 2025)
Poor adherence to photoprotection in xeroderma pigmentosum (XP) increases morbidity and shortens lifespan due to skin cancers.To test a highly personalized intervention (XPAND) to reduce the dose of ultraviolet radiation (UVR) reaching the face in adults with XP, designed using known psychosocial determinants of poor photoprotection.A two-arm parallel group randomized controlled trial, including patients with suboptimal photoprotection to receive XPAND or a delayed-intervention control arm that received XPAND the following year. XPAND comprises seven 1 : 1 sessions targeting photoprotection barriers (e.g. misconceptions about UVR) supported by personalized text messages, activity sheets and educational materials incorporating behaviour change techniques. The primary outcome, mean daily UVR dose to face across 21 days in June-July 2018, was calculated by combining UVR exposure at the wrist with a face photoprotection activity diary. Secondary outcomes were UVR dose to face across 21 days in August 2018, time spent outside, photoprotective measures used outside, mood, automaticity and confidence to photoprotect. Financial costs and quality-adjusted life years (QALYs) were calculated.Sixteen patients were randomized; 13 provided sufficient data for primary outcome analysis. The XPAND group (n = 8) had lower mean daily UVR dose to face [0.03 standard error of difference (SED) (SD 0.02)] compared with controls (n = 7) [0.43 SED (SD 0.17)] (adjusted difference = -0.25, P < 0.001, Hedge’s g = 2.21) at the June 2018 assessment. No significant between-group differences were observed in time spent outside, photoprotection outside, mood or confidence. The delayed-intervention control showed improvements in UVR dose to face (adjusted difference = -0.05; Hedge’s g = -0.1), time outside (adjusted difference = -69.9; Hedge’s g = -0.28) and photoprotection (adjusted difference = -0.23, Hedge’s g = 0.45) after receiving XPAND (June 2019 assessment). XPAND was associated with lower treatment costs [-£2642; 95% confidence interval (CI) -£8715 to £3873] and fewer QALYs (-0.0141; 95% CI -0.0369 to 0.0028).XPAND was associated with a lower UVR dose to face in patients with XP and was cost-effective.Xeroderma pigmentosum (XP) is a genetic condition that stops a person’s skin from repairing damage from ultraviolet radiation (UVR), and increases the risk of developing skin cancers. The only way to reduce this risk is to protect the skin by staying indoors and using items such as hats, glasses and sunscreen when outside. However, people with XP can find it difficult to protect their skin all the time.We designed an intervention (called XPAND) to support people with XP to improve photoprotection. This involved seven tailored conversations, using materials (e.g. a magazine), between a patient and a healthcare professional to identify what motivates them to protect their skin, and what makes it harder. We measured the amount of UVR reaching the face (dose to face), before and after XPAND, compared with a group that didn’t do the sessions. Our way of measuring was new, using a UVR monitor worn on the wrist and photoprotection recorded in a diary. The XPAND group had lower dose-to-face measurements afterwards than those who did not receive XPAND immediately, suggesting that it could be successful. However, because we were comparing small groups, we cannot be certain that the result was because of XPAND, or whether the group already had lower dose-to-face measurements.Overall, our findings from the assessment of value for money found that patients undergoing XPAND had lower service costs and similar outcomes to the comparison group.